Community disparities in out of hospital cardiac arrest care and outcomes in Texas. (June 2021) - Huebinger, Ryan; Vithalani, Veer; Osborn, Lesley; Decker, Cameron; Jarvis, Jeff; Dickson, Robert; Escott, Mark; White, Lynn; Al-Araji, Rabab; Nikonowicz, Peter; Villa, Normandy; Panczyk, Micah; et al.
Abstract: Background: Large racial and socioeconomic inequalities exist for out-of-hospital cardiac arrest (OHCA) care and outcomes. We sought to characterize racial, ethnic, and socioeconomic disparities in OHCA care and outcomes in Texas. Methods: We analyzed 2014–2018 Texas-Cardiac Arrest Registry to Enhance Survival (CARES) data. Using census tracts, we defined race/ethnicity neighborhoods based on majority race/ethnicity composition: non-Hispanic/Latino white, non-Hispanic/Latino black, and Hispanic/Latino. We also stratified neighborhoods into socioeconomic categories: above and below the median for household income, employment rate, and high school graduation. We defined outcomes as bystander CPR rates, public bystander AED use, and survival to hospital discharge. Using mixed models, we analyzed the associations between outcomes and neighborhood (1) racial/ethnic categories and (2) socioeconomic categories. Results: We included data on 18, 488 OHCAs. Relative to white neighborhoods, black neighborhoods had lower rates of AED use (OR 0.3, CI 0.2–0.4), and Hispanic/Latino neighborhoods had lower rates of bystander CPR (OR 0.7, CI 0.6–0.8), AED use (OR 0.4, CI 0.3–0.6), and survival (OR 0.8, CI 0.7–0.8). Lower income was associated with a lower rates of bystander CPR (OR 0.8, CI 0.7–0.8), AED use (OR 0.5, CI 0.4–0.8), and survival (OR 0.9, CI 0.9–0.98). Lower high school graduation was associated with a lower rate of bystander CPR (OR 0.8, CI 0.7–0.9) and AED use (OR 0.6, CI 0.4–0.9). Higher unemployment was associated with lower rates of bystander CPR (OR 0.9, CI 0.8–0.94) and AED use (OR 0.7, CI 0.5–0.99). Conclusion: Minority and poor neighborhoods in Texas experience large and unacceptable disparities in OHCA bystander response and outcomes.